2024
DOI: 10.3390/electronics13030536
|View full text |Cite
|
Sign up to set email alerts
|

Efficient EM Scattering Modeling from Metal Targets Coated with Anisotropic Thin Layers

Mengbo Hua,
Siyuan He

Abstract: To address the challenges posed by composite targets composed of an anisotropic medium and metal in electromagnetic (EM) scattering calculations, this paper introduces an innovative hybrid algorithm tailored for simulating the EM scattering characteristics of such complex targets. Utilizing impedance boundary condition (IBC), the method employs surface impedance vectors to precisely depict the EM properties of the medium. By harnessing the distinct advantages of the Method of Moments (MoMs) at low frequency an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 40 publications
(57 reference statements)
0
3
0
Order By: Relevance
“…It can be observed that after the LFM signal undergoes matched filtering, its form changes from a wide pulse with a large time-bandwidth product to a narrow pulse. Additionally, the compression ratio r of LFM is equal to the product of the signal's timebandwidth product, as shown in Equation (13).…”
Section: Linear Frequency-modulated Signalmentioning
confidence: 99%
See 2 more Smart Citations
“…It can be observed that after the LFM signal undergoes matched filtering, its form changes from a wide pulse with a large time-bandwidth product to a narrow pulse. Additionally, the compression ratio r of LFM is equal to the product of the signal's timebandwidth product, as shown in Equation (13).…”
Section: Linear Frequency-modulated Signalmentioning
confidence: 99%
“…Moreover, inverse imaging algorithms for SAR based on time-domain stepped-frequency radar methods were introduced [8][9][10][11]; these involved replacing linear frequency-modulated pulse excitation with Gaussian pulses, demodulating scattering echo data, compressing pulses, and performing the azimuth inverse fast Fourier transform (IFFT) to obtain radar wideband echo signals. Additionally, a range of efficient EM scattering domain PO modeling methods were proposed for single/multi-layer anisotropic medium-coated metal conductor targets [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation